A Controlled Trial of Sustained-Release Bupropion, a Nicotine Patch, or Both for Smoking Cessation - Jorenby, Douglas E; Leischow, Scott J; Nides, Mitchell A; Rennard, Stephen I; Johnston, J. Andrew; Hughes, Arlene R; Smith, Stevens S; Muramoto, Myra L; Daughton, David M; Doan, Kimberli; Fiore, Michael C; Baker, Timothy B (The New England journal of medicine, 1999)
Each year, approximately 20 million of the 50 million smokers in the United States try to quit smoking, but only about 6 percent of those who try succeed in quitting in the long term. 1 Nicotine-replacement therapies, such as the nicotine patch and nicotine gum, boost the rates of smoking cessation by a factor of 1.4 to 2.6 in comparison with placebo treatments, 2 but 70 to 80 percent of smokers who use these therapies still start to smoke again. Affect or mood appears to exert potent effects on the motivation to use nicotine. 3 – 5 For instance, among smokers, symptoms of nicotine . . .